Blockchain-Powered Peer-to-Peer Energy Trading: A Research Frontier - Panchajanya Mysarla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the emerging field of blockchain-powered peer-to-peer energy trading and its potential to revolutionize the global energy sector. It examines the fundamental principles of decentralized energy marketplaces, including smart contracts and distributed ledger technology, which enable secure, transparent, and efficient energy transactions. The article highlights key research breakthroughs, such as AI-managed trading platforms that optimize supply and demand in real-time, and presents case studies from pilot projects in Europe, the United States, and Australia. Future innovations, including tokenized energy credits and cross-border renewable energy exchanges, are discussed alongside their potential impact on energy markets. The article also addresses regulatory considerations and strategies for large-scale adoption in both national and international contexts. Long-term implications for sustainability and market transparency are explored, emphasizing blockchain’s role in facilitating the transition to renewable energy sources and creating a more open and equitable energy economy. This comprehensive article underscores the transformative potential of blockchain technology in addressing critical challenges in energy distribution, market efficiency, and environmental sustainability.